The Role of Integrated Science Learning Modules in Training Teaching Skills for Prospective Teachers - Sauqina Sauqina; Yasmine Khairunnisa; Ellyna Hafizah; Ratna Yulinda; Mella Mutika Sari; Muhammad Fuad Sya'ban (Universitas Lambung Mangkurat, 2025)
Integrated science education requires prospective teachers to incorporate various educational elements into their teaching practices. Students in the Science Education Program at FKIP ULM encounter challenges when planning science lessons that blend different concepts, contexts, and skills into a cohesive learning experience. To tackle this challenge, the researcher created a teaching module that provides guidance on integrating science education using two of Robin Fogarty's curriculum integration models: the connected model and the nest model. This study seeks to examine the module's role in developing teaching skills. It employs a qualitative methodology with case study approach, focusing on the experiences of sixth-semester science education students during their teaching. Data were gathered through semi-structured interviews, utilizing theoretical sampling until saturation was reached. The analysis was conducted using Charmaz’s grounded theory approach and then discussed from the perspective of Teaching Mastery Framework (TMF). The findings indicate that the developed integrated science education module can support prospective teachers in planning of teaching practice, especially in teachers pedagogical content knowledge (PCK) and developing lesson plan